Use of a dual biosensor for identification of novel secretion signal peptides and efficient screening of precision fermentation production strains. - Parastoo Karimian; Ema Johnston; Annette Kasprzak; Jian-Wei Liu; Sally Stockwell; Thomas Vanhercke; CarolJ. Hartley (Future Foods)
Methylotrophic yeast Pichia pastoris (Komagaetella phaffii) has emerged as a versatile and robust host for recombinant protein production, owing to its capacity for high-level protein expression, scalability, and post-translational protein modifications. The development of efficient genetic tools, expression vectors and high throughput screening techniques is critical for leveraging the full potential of P. pastoris in both research and industrial applications. We have developed a dual biosensor enabling both high throughput screening of base precision fermentation production strains and assessment of genetic components for recombinant protein expression and secretion in P. pastoris using a dual bioluminescence-esterase system. The biosensor system is based on the combination of a split bioluminescence system (HiBit, Promega) with a versatile and thermostable esterase enzyme (E2Aa). Our results demonstrate the multiple uses of this system. The dual biosensor enabled identification and assessment of optimal genetic components such as novel secretion signal peptides derived from a fungal pathogen. In addition, we demonstrate the usefulness of the biosensor for screening and identifying suitable base production strains for recombinant production of target enzymes and proteins, including difficult-to-quantify, intrinsically-disordered animal proteins, such as caseins. In future, we aim to expand the utility of this system to assess the effect of additional genetic edits to Pichia pastoris base production strains and to demonstrate applicability towards screening and optimizing precision fermentation strains for other yeast and fungal species.